Material compatibility, environmental impact, and safety considerations of hydrogen as a sustainable motor fuel - Chen, Linfei; Boichenko, Sergii (Національний технічний університет "Харківський політехнічний інститут", 2025)
Hydrogen is emerging as a promising sustainable alternative to traditional fossil fuels in the transport sector. This paper examines the material compatibility, environmental impact, and safety considerations associated with hydrogen as a motor fuel. Key findings indicate that hydrogen, when produced via green hydrogen methods, offers significant environmental benefits by reducing carbon emissions. However, material degradation, especially hydrogen embrittlement in metals and composites, presents challenges for the long-term durability of storage and fuel systems. Additionally, safety concerns related to flammability, leakage, and high-pressure storage require robust safety protocols and advanced technologies. The study recommends further research into hydrogen-resistant materials, scalable production technologies, and enhanced safety systems to enable the large-scale adoption of hydrogen as a clean energy source in the transportation sector.
Keywords: Hydrogen; Sustainable Fuel; Material Compatibility; Green Hydrogen; Hydrogen Embrittlement; Safety Considerations